Penipuan dalam pendaftaran urusniaga tanah di Semenanjung Malaysia: satu analisa perundangan - Khuzaimah, Mat Salleh (2023)
The problem of fraud in land dealings is a severe problem in Malaysia. From 2012 until 2019, there were 562 cases of land dealing fraud reported throughout the country. The National Land Code 1965 provides the law regarding fraud in land dealing, which states a person's title to property can be defeated when the element of fraud, forgery and misrepresentation exist during the title’s registration process. Thus, this study aims to analyse the law relating to land dealing, the registration procedure and its relation with fraud. Fraud in land dealing occurs when the identity of the landowner has been defrauded, or forgery unto the registration documents, forgery on the power of attorney letter, court order and lawyer’s misconduct. Apart from this, false registration process at the land office also contributed to this problem. Therefore, this study scrutinised the registration procedure to discover its relation with land fraud. The finding also revealed that the National Land Code did not provide a remedy to the land fraud victims. Therefore, this study examined the necessity to provide a remedy for the victim. The methods used are legal and socio-legal research by analysing relevant sources and documents, including scholarly works and official reports. Interviews are also conducted with the land office officials, police and lawyer to understand the registration procedures and their relation with land fraud. This study found that the states of Kedah and Perak recorded an alarming number of land fraud.cases. Despite both states have implemented the biometric system as a verification or finger print record for the applicant of the dealing, yet fraud cases still occur, causing the victims to suffer losses. Thus, this study proposed that the law relating to the registration and procedure need to be tightened by the right interpretation of law by the court and the registration procedures been followed strictly based on the prescribed module. In providing a remedy to the victim,National Land Code has to be amended to safeguard the interest of land fraud victim. For this purpose, the study recommended Malaysia to follow good practices implemented in Australia and Singapore as the best practice model.